Unit of Expression in Land and House Sale Ads on Facebook social media - Sudiyati, Citra Amelia; Rustono, Rustono; Baehaqie, Imam (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study discusses communication carried out in the realm of trade; one form of communication is advertising. The purpose of this study is to find various forms, meanings, and functions of units of expression in advertisements for buying and selling land and houses on Facebook social media. The method used is the listening method with free listening techniques, proficient involvement and recording techniques. The results of this study are units of expression for advertising the sale and purchase of land and houses in the form of forms consisting of words, phrases, abbreviations, acronyms, and reduplication. Furthermore, the meaning of the unit of expression for advertising the sale and purchase of land and houses consists of lexical meaning and grammatical meaning. Then, the function of the unit of expression for buying and selling land and houses consisting of aesthetic functions, directive functions, and informational functions. In advertisements for the purchase and sale of real estate and homes, the aesthetic function is employed as an attraction or as a supporting element to draw in prospective purchasers. Advertisements for buying and selling land and homes use the directive function to entice potential customers to visit marketing galleries and persuade them to make a purchase. When a product or service is advertised, the informational function is utilized to inform potential customers of its benefits. The findings of this study are hoped to aid in the growth of semantic science, particularly in the investigation of language form, meaning, and function.